Digging for Stress-Responsive Cell Wall Proteins for Developing Stress-Resistant Maize - Niu, Liangjie; Liu, Lunyu; Wang, Wei (Frontiers in Plant Science, 2020)
As a vital component of plant cell walls, proteins play important roles in stress response by modifying the structure of cell walls and involving in the wall integrity signaling pathway. Recently, we have critically reviewed the predictors, databases, and cross-referencing of the subcellular locations of possible cell wall proteins (CWPs) in plants (Briefings in Bioinformatics 2018;19:1130–1140). Here, we briefly introduce strategies for isolating CWPs during proteomic analysis. Taking maize (Zea mays) as an example, we retrieved 1873 probable maize CWPs recorded in the UniProt KnowledgeBase (UniProtKB). After curation, 863 maize CWPs were identified and classified into 59 kinds of protein families. By referring to gene ontology (GO) annotations and gene differential expression in the Expression Atlas, we have highlighted the potential of CWPs acting in the front line of defense against biotic and abiotic stresses. Moreover, the analysis results of cis-acting elements revealed the responsiveness of the genes encoding CWPs towards phytohormones and various stresses. We suggest that the stress-responsive CWPs could be promising candidates for applications in developing varieties of stress-resistant maize.